Night Sweats as a Prominent Symptom of a Patient Presenting with Pulmonary Embolism - Attila Feher; Saif A. Muhsin; Anna M. Maw (Case Reports in Pulmonology)
Pulmonary embolism is a common, potentially fatal disease. Making the correct diagnosis early can significantly reduce mortality and morbidity. We report the first case of drenching night sweats as one of the presenting symptoms of submassive pulmonary embolism. One week after undergoing laparotomic sigmoidectomy for diverticulitis, our patient started to experience drenching night sweats and pleuritic back pain. CT identified bilateral main stem pulmonary artery emboli, and treatment was initiated with subcutaneous enoxaparin injections. Imaging and laboratory workup failed to reveal any other explanation for the night sweats. Patient was discharged on rivaroxaban, and he reported complete resolution of symptoms upon the 3-month follow-up visit and 9-month follow-up call. Based on our case we propose night sweats to be a potential presenting symptom of pulmonary embolism. Our observation can help make an earlier diagnosis of pulmonary embolism.